Influence of Consumer Behavior and Marketing Mix on Product Purchasing Decisions - Dewi, Faye Maya; Sulivyo, Lod; Listiawati; Dewi, Faye Maya Dewi (Pandawan, 2022)
The purpose of the study was: 1) to look at the direct influence between consumer behaviour on the marketing mix, 2) to look at the direct relationship between consumer behaviour on purchasing decisions, 3) to look at the influence of direct relationships between marketing mixes on purchasing decisions, 4) to look at the indirect influence of indirect relationships between consumer behaviour toward purchasing decisions mediated by the marketing mix. The sample used in the study was as many as 120 randomly selected respondents, and data processing using Smart PLS 2.0 software. The results of this study are, 1) consumer behaviour towards the marketing mix has a positive and significant influence with a relationship value of 55,899 > 1.96. 2) Consumer behaviour towards purchasing decisions has a positive and significant influence with a relationship value of 2,850 > 1.96. 3) Marketing mix on purchasing decisions has a positive and significant influence value with a relationship value of 13,764 > 1.96. 4) The results of analysis of indirect influence pathways between consumer behaviour to purchasing decisions mediated by marketing mix is 13,554 > 1.96 with a significance level of 5% proving that marketing mix has a significant effect in mediating the relationship between consumer behaviour to purchasing decisions.